Separation of low-intensity magnetic anomalies and its interpretation - Грищук, П. І.; Гура, К. О.; Нурмухамедов, В. Г. (Київський національний університет імені Тараса Шевченка, 2005)
in the article the separation of low-intensity magnetic anomalies with method of averaging is executed. The selection of anomalies is analyzed for different radiuses of sliding window. The optimum radius of averaging is certain. Comparison of interpretation of the magnetic anomalies is executed at determination of their background constituent through spline and method of averaging.

Розглянуто питання виділення слабоінтенсивних магнітних аномалій за допомогою методу осереднення. Проаналізовано застосування для виділення аномалій різних радіусів ковзного вікна. Визначено оптимальний радіус осереднення. Виконано порівняння інтерпретації магнітних аномалій при визначенні їх фонової складової за допомогою сплайну та методу осереднення.
Виділення слабоінтенсивних магнітних аномалій та їх інтерпретація
Keywords: магнітні аномалії; слабоінтенсивні магнітні аномалії; інтерпретація магнітних аномалій; метод осереднення; ковзне вікно; магнітне поле; геофізична обробка даних; magnetic anomalies; low-intensity magnetic anomalies; magnetic anomaly interpretation; averaging method; sliding window; magnetic field; geophysical data processing